The effect of trade related environmental measures on the forest sector and timber trade of Peninsular Malaysia - Shanmugam, Sugumari (2015)
Global concern on illegal logging has led to the imposition of binding trade related environmental measures on trade of timber and timber products by developed countries like the US, EU and Australia. This dissertation examines the effect of the binding measures on Peninsular Malaysia’s forest sector and timber trade. Putnam’s two-level game theory is applied, to demonstrate the interdependence of politics at the international level with the domestic level. There is a need to have a “win-set” between the international and domestic levels whereby an agreement reached by stakeholders at Level II (discussions at the domestic level) will help to make the bargaining at Level 1 a success (bargaining between negotiators which leads to a tentative agreement). In the case of Peninsular Malaysia’s forest sector and timber trade, it has been acknowledged that the measures imposed by the EU through FLEGT VPA/EUTR and to a lesser extent by Australia through its ILPA/ILPAR as well as the US with its Lacey Act amendments, have brought about changes in policy and administration.